The Effect of Gadgets on Cognitive Development of Children Age 5-6 Years In Sirimau Sub-District, Ambon City - Lisa. M. Sahetapy (Peneliti.net, 2021)
This study aims to determine the effect of gadgets on cognitive development of children aged 5-6 years in Sirimau sub-district, Ambon City. This research needs to be discussed because gadgets affect the cognitive development of children aged 5-6 years. The population in this study were 30 parents of children aged 5-6 years in Sirimau sub-district who were selected using purposive sampling technique. The research design used is quantitative research using Discrimination Power Test, Validity and Reliability Test with an emphasis on theory testing through measurement of research variables through the distribution of research questionnaires. The sampling technique used was purposive sampling. The analysis technique used is simple linear regression with SPSS 16.0 software. The results of this study indicate that the gadget variable. The gadget variable affects cognitive development by 85.6% and the remaining 14.4% is influenced by other variables not examined in this study.